THE INITIAL DESIGN OF THE SPIRITUAL MODEL PRENEURSHIP AS A SOCIAL SPIRITUAL ENTREPRENEURSHIP LEARNING FOR HIGHER EDUCATION - Muhammad rifai, Muhammad rifai; Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Ricky Yoseptry, Ricky Yoseptry; Noneng Nurhayani, Noneng Nurhayani; Muhajirin, Muhajirin; Utama, Utama; Nurrohman, Nurrohman; Devonian Isyan Nabila, Devonian Isyan Nabila (Media Nusantara, 2024)
Tri Dharma PT, which mandates higher education lecturers by involving students to carry out teaching that is developed into research, the results of which are directed towards community service. Research in the field of entrepreneurship that is imbued with the Vision and Mission of going to higher education that builds aspects of spirituality / professional ethics / soft skills for students is developed to be applied to communities affected by Covid 19 to become a village empowerment program with all components of society. The concept of entrepreneurship based on soft skills with the packaging of the university's vision and mission which has a specific spirituality is developed into a model of Spiritual preneurship. The initial concept of this learning is in line with the "Merdeka Belajat" program by combining the concepts of Student Base Learning and Project Base Learning. Spiritual preneurship is a model that develops village entrepreneurship with student organizations, supervisors and community components that include social entrepreneurial values, entrepreneurship based on the Halal Product Industry, sourced from syar'I finance, with harmonious efforts to protect the environment (Eco -Preneurship), by utilizing communication technology, information and appropriate technology (Techno Preneurship) while still embracing and empowering local wisdom (Ethno-Preneurship) This research uses the method of literature study, observation and brainstorming. Observation and brainstorming were carried out in a pilot village, namely Cikahuripan Village, Cimanggung District, Sumedang Regency. This village was badly hit by the pandemic outbreak with the massive layoffs of its people who work in the wood manufacturing sector.